I get confused only at the very end of this problem...I got the answer from the book:
(*= radical sign)
= 5 *3 - 2 *3
=(5 - 2) *3
= 3 *3
My question is: where does the other *3 go? Why is there only one *3 in the final answer?
I get confused only at the very end of this problem...I got the answer from the book:
(*= radical sign)
= 5 *3 - 2 *3
=(5 - 2) *3
= 3 *3
My question is: where does the other *3 go? Why is there only one *3 in the final answer?
The answer is: it's still there! You start off with two square roots of three being subtracted from five square roots of three. You are then left with three square roots of three, because 5 of something minus 3 of something is 2 of that something.
There may only be one radical in the final answer, but it is being multiplied by three, which is the same as adding it to itself twice.